Pengaruh Kombinasi Cangkang Kemiri Dengan Tempurung Kelapa Terhadap Nilai Kalor Briket - Idris, Muhammad; Hermawan, Indra; Sihombing, Verianto (CV. IRA PUBLISHING, 2022)
Energy demand in the world continues to increase in line with population growth and economic growth. Biomass is a renewable energy source that comes from living things which include plants, animals and their by-products such as garden waste, crops and so on. The mass of 0.0002 kg is the mass of the briquettes allowed on the bomb calorimeter test equipment, the test was carried out nine times for each variation of the mixture, where there were three variations of the mixture in the test, namely level 1 variation of the mixture of 25% candlenut shell charcoal, 65% coconut shell charcoal and 10% starch, level 2 variation mix 65% candlenut shell charcoal, 25% coconut shell charcoal and 10% starch, level 3 mixed variation 45% candlenut shell charcoal, 45% coconut shell charcoal and 10% starch . Briquettes are fuel that is compacted and formed in molds. The results of the analysis data were obtained using Minitab20 with product optimization of the Taguchi method. The optimum LHV value of the briquettes recommended by Taguchi was obtained from the mixed variation level 2 briquettes, namely 65% ​​candlenut shell charcoal and 25% coconut shell charcoal with an adhesive concentration of 10%, obtained a heat of 23884.252 kJ/kg against the uncontrol factor during briquette drying, namely speed wind 0.5 m/s, ambient temperature 37.4 °C, with air humidity 46% while in laboratory observations the optimum LHV value was in level 3 mixed variation briquettes with a value of 32054.208 kJ/kg with mixed variations namely 45% candlenut shell and 45% coconut shell charcoal with an adhesive concentration of 10% starch.